Effect of water diffusion and thermal coupling condition on SBS modified asphalts' surface micro properties. (1st March 2021) - Gong, Yan; Xu, Jian; Chang, Rong; Yan, Er-hu
Highlights: The effects of water-thermal conditions are investigated by AFM and FTIR. Moisture-thermal sensitivity can be well described by moisture oxygenated index. Both polar compounds and SBS polymers affect the moisture-thermal sensitivity. Diffusion process characterized by moisture oxygenated index follow Fick's law. Abstract: Moisture damage is a particular concern for asphalt aging during the service life of asphalt mixture and pavement. At present, the microscopic research of the surface morphology, mechanical property and chemical composition of SBS modified asphalts under the water diffusion and thermal coupling condition is lacking. In order to characterize the effect of water diffusion-thermal condition on surface micro properties and moisture sensitivity of SBS modified asphalts, atomic force microscopy (AFM) and Fourier transform infrared spectroscopy (FTIR) were used in this paper. Both SBS modified and Pen70 asphalts showed the similar evolution under the water diffusion-thermal coupling condition from AFM images. FTIR tests confirmed that the polar compounds increased and SBS polymer decreased in SBS modified asphalts. Meanwhile, the increasing exposure temperature would accelerate the evolution of the chemical composition and surface structure. What's more, combined with AFM and FTIR tests results, it was found that the formation of microstructure and the micromechanical properties were closely related to the chemical functional group indexes. The ratio of modulus between wet-conditioned sample and dry sample was proposed to evaluate the SBS modified asphalts' moisture-thermal sensitivity. The interactions between polar compounds with water molecules and the reduction of SBS polymers were collectively responsible for the arise of the surface modulus and moisture-thermal sensitivity of SBS modified asphalt. In addition, the diffusion of water in asphalt films followed Fick's second law. It was found that the water molecules diffused slower in SBS modified asphalt, which might be associated with the interaction between water molecules and SBS modifier.